Diagnostic Evaluation Low Yield for Patients with a Lower-Risk Brief Resolved Unexplained Event - Haddad, Rita (Glob Pediatr Health, 2021)
In contrast to patients with an apparent life-threatening event (ALTE), the American Academy of Pediatrics recommends very limited evaluation for patients categorized as lower-risk brief resolved unexplained event (BRUE). This retrospective review aims to explore potential missed diagnostic opportunities for patients with a lower-risk BRUE (n = 10) through comparison with a subset of patients with ALTE (n = 72). None of the patients with a lower-risk BRUE had laboratory, imaging or ancillary studies that were diagnostic. Among patients with ALTE, 5 had laboratory and 3 had imaging studies that were diagnostic. None of the patients with a lower-risk BRUE had recurrent events during hospitalization or a serious underlying diagnosis identified within the 90 day follow-up period. As recommended by the AAP, patients with a lower-risk BRUE do not need diagnostic evaluation and can be discharged home with outpatient follow-up.